PENGARUH KOMITMEN DAN MOTIVASI TERHADAP KEMAMPUAN DAN KINERJA DOSEN (Studi Kasus Bidang Ilmu Eksakta) - Riandika Putra, Gevin Meirio (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to determine the influence of commitment and motivation towards the capability and performance of the exact sciences lecturer at Faculty of University of Riau. As the dependent variable is the performance and capabilities, while the independent variable is the commitment and motivation. The method of analysis used in this study is descriptive statistical analysis method and multiple regression analysis.This study used a survey method, where a population of as many as 544 lecturers Riau University Faculty of exact sciences, taken a sample of 230 respondents with a stratified random sampling technique. Before testing the hypothesis, test the validity and reliability of the primary data questionnaire using SPSS version 17.0. Regression equations were then tested with analysis of classical assumption of normality test, multicollinearity test, heteroskidastity test and autocorrelation test. Analysis of the influence of the independent variables with the dependent variable analysis performed with the t test, F test, the coefficient determinant (Adjusted R2) and correlation coefficient (R).The results showed partially and simultantly, commitment and motivation factors have an influence on the ability. Variable commitment, motivation and ability to partially and together have an influence on performance. The path analysis demonstrated a commitment to have a dominant influence on the performance that is equal to 48.2%, whereas 16.4% of the motivation and capability factor of 14.4%.Keywords: Commitment, Motivation, Ability, Performance